Konsep Etika Guru Perspektif Al-Bukhari; Studi atas Kitab Sahih al-Bukhari Karya Abu ‘Abdillah Muhammad bin Ismail al-Bukhari - Ahmad Junaedy (Jurnal Ilmiah Iqra', 2021)
The Concept of Teacher Ethics in Al-Bukhari's Perspective; Study of the Book of Sahih al-Bukhari by Abu 'Abdillah Muhammad bin Ismail al-Bukhari. This paper aims to discuss study of hadist about the concept of ideal teacher offered by Muhammad bin Ismail al-Bukhari in his book, Shahih al-Bukhari, and also relevant to the professionalism of Islamic Education Teacher in basic constitusion about teacher and lecturer No. 14 Tahun 2005. The method used is library research by applying content analysis technique in discussion of teacher’s etihc in al-Bukhari’s perspective. And the conclusion in this paper tahat is a teacher must have nature of sincerity, knowledge, concern, compassion, pay attention to student, patient, fair, no discriminating and responsible. Ant this relevant to the professionalism of Islamic education teacher.